La propiedad privada y su índole elástica - Muñoz Catalán, Elisa (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2014)
With this work we intend to study the social-legal onlook onto homosexual marriage, its constituent requirements, its components and the role that the active subject as well as the passive one have played in this kind of sexual relationships as much in the active as in the passive subject, in the effeminate or lacking the virility associated to a Roman citizen type, starting from the classic period also known as the big splendor of the Roman Empire until its current regulation in the Spanish legal system. In this sense, we have tried to comparatively look into the requirements which made the basis for the historically legally approved Roman marriage as opposed to the currently common homosexual, bisexual or even lesbian marriages; making a special note on the lack of legal capacity of the parties, as well as in the treatment that has traditionally had the physical incapabity to reproduce, because of the impotentia generandi associated to one single sex marriages.